Propuesta de espacios ecológicos utilizando un sistema de cosecha de lluvia de los techos de los edificios en el Cementerio Metropolitano de Pavas, San José Costa Rica - Pereira-Jiménez, María Fernanda; Mora-Vega, Noily Sofía (Instituto Tecnológico de Costa Rica, 2018)
Green spaces are considered the lungs of cities, they allow to maintain the relationship between the inhabitants and nature while improving population´s health through air purification. They collaborate so that the aquifer mantle maintains the humidity of the soil and serves as a link between environment and population. Green areas grow in importance, since they are considered a significant factor in the health and well-being of the urban inhabitant. The proposal consists of converting the Metropolitan Cemetery Park into a lung of Pavas to optimize the space and honor the memory of the loved ones, while environment is protected through an irrigation system in which the alternative of harvesting rain from roofs is analyzed as a permanent source of water for irrigitation during the dry season. This work consists of two sections, of which the fisrt introduces the design of an ecological park in the green areas of the CampoSanto in the Metropolitan Cemetery where the creation of islands with different species (arboreal, ornamental) show a harmonious site expressing its scenic beauty.The second section addresses the design of an irrigation system that uses rainwater collected as a permanent source. In the analysis carried out, it is estimated that during the rainy season from April to November, approximately 1.100 m3 of water could be catched and stored.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2018
Keywords: Diseño; Cementerio; Silvicultura; Desarrollo; Áreas